The urgent need for disability studies among midlife adults - Carrie A. Karvonen-Gutierrez; Elsa S. Strotmeyer (BMC, 2020)
Abstract Issues of poor physical functioning and disability are burdensome for midlife adults and evidence suggests that the prevalence of these conditions is increasing temporally. Physical functioning during the midlife period, however, may be highly amendable to intervention given the highly dynamic nature of functioning during this life stage. Thus, efforts to improve or forestall poor physical functioning and/or disability during midlife may not only improve the health status and quality of life for midlife adults but may have important ramifications on the health of these individuals who will become older adults in the future. This thematic series on women and disability includes contributions addressing issues of person, place and time with respect to disability in midlife and into late adulthood. The purpose of this commentary is to provide a summary overview of the major themes of the series and to offer insight into areas of most promise for intervention among midlife populations to improve physical functioning and prevent disability.